2014
DOI: 10.1177/0969733014542679
|View full text |Cite
|
Sign up to set email alerts
|

Researching moral distress among New Zealand nurses

Abstract: The results imply that moral distress in nursing remains a highly significant and pertinent issue that requires greater consideration by health service managers, policymakers and nurse educators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
2
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 36 publications
4
62
2
9
Order By: Relevance
“…Several studies have been conducted to determine the validity and reliability of the different versions of the scale in different countries. 17,33,39,45,55,[61][62][63] In line with the wide use of the scale in many studies, the moral distress scale was preferred in our study too.…”
Section: Moral Stress Related Factors and Causesmentioning
confidence: 92%
See 1 more Smart Citation
“…Several studies have been conducted to determine the validity and reliability of the different versions of the scale in different countries. 17,33,39,45,55,[61][62][63] In line with the wide use of the scale in many studies, the moral distress scale was preferred in our study too.…”
Section: Moral Stress Related Factors and Causesmentioning
confidence: 92%
“…6,[25][26][27][28][29][30] The last one is that person-specific systematic care cannot be planned and thus cannot be provided. 28 Among the other factors that cause moral distress are the effects of paternalistic healthcare system, 31,32 lack of effective communication and team collaboration, [28][29][30][33][34][35] lack of clear task descriptions related to the treatment and care in these areas, and inadequate staff and increased workloads. 28,33,35,36 Another factor that significantly causes moral distress is that nurses are not the professionals taking part in the decision-making but they just put the already made decisions into practice.…”
Section: Introductionmentioning
confidence: 99%
“…Although just under half had never considered quitting or leaving a position, one third of participants had considered leaving a position and almost one quarter stated that they had left a position because of moral distress. This is similar to Woods et al (2014) who reported 48% of their participants as having considered leaving nursing (across a range of general care settings), but higher than Silen et al (2011) who found 20% of participants had considered leaving (hospital care setting). So while findings in our study are not as high as some, one third of participants having considered leaving a position because of moral distress is significant.…”
Section: Phase 1: Measuring Moral Distresssupporting
confidence: 81%
“…These items in ranked order were: (1) Woods, Rodgers, Towers and Grow (2014). In that study (1) work with nurses who are less than competent was identified as their third most frequent cause of moral distress, and (2) witness diminished client care quality due to poor team communication emerged as causing the second highest level of intensity of moral distress.…”
Section: Phase 1: Measuring Moral Distressmentioning
confidence: 87%
See 1 more Smart Citation